Pengaruh Migrasi Masuk Dan Investasi Terhadap Pengangguran Di Kota Pekanbaru - Noorfath Hasanah; Harlen '; Hainim Kadir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Unemployment is the macroeconomic problems that affect humans directly and is a complex problem that requires analysis to obtain a solution to unemployment or at least reduce unemployment. This study aimed to examine the effect of migration on unemployment entry and investment in the city of Pekanbaru. This research uses secondary data. analysis of the data in this study using multiple linear regression method. hypothesis testing using partial test (t test), simultaneous (f test), test correlation coefficient (R) and test the coefficient of determination (). the data used in this study are data on the number of unemployed, the number of migrations and the amount of investment in the city of Pekanbaru 2002-2011.The results of the testing that has been done, the entire regression test showed that all independent variables have no significant effect on the dependent variable. individual regression test showed that the number of in-migration does not significantly influence the number of unemployed in the city of Pekanbaru, and investment also no significant effect on the number of unemployed in the city of Pekanbaru. The magnitude of the effect caused by the two independent variables together on the dependent variable of 38.7%, while the remaining 61.3% is influenced by other variables not examined in this study.Keywords: unemployment, in-migration, investment.